First characterization of functionalized nanoparticles—tandem of biosynthesized silver nanoparticles conjugated with piperine - Smilkov, Katarina; Gjorgieva Ackova, Darinka; Cvetkovski, Aleksandar; Geskovski, Nikola; Pejova, Biljana; Boev, Blazo; Makreski, Petre (Chemical Papers, Springer, 2022)
The present work outlines the biosynthesis of silver nanoparticles (AgNPs) using black pepper fruit extract (piperine) as bioreductive and capping agent, followed by their conjugation with piperine and characterization thereof. Several approaches for elucidation of the properites of both non-conjugated and piperine-conjugated AgNPs were implemented. The formation of silver nanoparticles was monitored at 420 nm, corresponding to the surface plasmon resonance band of the obtained AgNPs. SEM and AFM analyses demonstrated the spherical shape of the NPs, while the DLS analysis revealed the negative charge of the NPs with mean diameter of 116.6 ± 8.9 nm and 142.1 ± 10.7 nm for AgNPs and piperine-conjugated AgNPs, respectively. Characteristic Raman bands at 237 cm−1 for AgNPs and at 249 cm−1 for piperine-AgNPs, indicate Ag+ reduction to nanoscaled Ag, in addition to emergence of new bands as a result of the formation of bonds with oxygen atoms from the extracted organic molecules. The bands in the Amide I region characteristic for β-sheets in the structure, followed by bands from the α-helices were also assigned. The work represents the first conjugation of the AgNPs with bioactive piperine, that further might be evaluated as promising new delivery system in the pharmaceutical and biomedical industry.
Keywords: Biosynthesized nanoparticles, Silver nanoparticles, Piperine, Plant bioactive